THE EXPOSITION COMPLEX OF THE MEMORIAL MUSEUM “ALZHIR” - Turgunbayev, Y. M.; Abaeva, M. D. (Journal of history, 2018)
This article describes the history and expositional structure of museum memorial complex of political repressions and totalitarianism victims. It covers the period of time since the formation of “the 26th point of” village of labor camps before the opening of the museum on behalf of the President of Kazakhstan Nursultan Nazarbayev in 2007 on 31 May. The author describes the main features of the exhibition is dedicated to the history of the origin, development and decline of the system of labor camps the most important component, the state machine in the 1930-50 its politico-administrative and economic role. The author describes in detail each composition. Particular attention is paid to the monument “Arch of sorrow” authored by famous Kazakhstani architect and designer Saken Narynov. In the three-story museum, all exhibits will be shown in a circular form, which will allow visitors to have a rich history of the same horrifying history.